Water quality of the Paraná river in a bathing resort region: a discussion on the potential impacts of secondary treated wastewater discharge - Ribeiro, Natasha Ulhiana Ferreira [UNESP] (2022)
The headwater of the Paraná River became the recipient water body for the Aparecida do Taboado’s Wastewater Treatment Plant effluents — Mato Grosso do Sul — in a project started in 2013 and completed in 2020. The emissary is located upstream of a bathing resort. This study aimed to monitor the river water quality before discharge starts, from August 2019 to February 2020. The CETESB Water Quality Index and its calculation parameters were used. The Paraná River presented good water quality (Water Quality IndexCETESB ≥72) and the absence of Escherichia coli. Nevertheless, 57 and 61% of the samples did not meet CONAMA Resolution No. 357/05 for biochemical oxygen demand and total phosphorus, respectively. Potential negative impacts on the water quality are related to the parameters of biochemical oxygen demand, total phosphorus and Escherichia coli and the secondary treated wastewater discharge into Paraná River may result in the water quality deterioration, compromising its multiple uses.